2005
DOI: 10.1007/s00268-005-7695-2
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Respiratory Effects of Robot‐assisted Laparoscopic Fundoplication in Children

Abstract: Laparoscopic fundoplication is increasingly used for treating gastro-esophageal reflux disease in children. Mechanical and pharmacological effects may contribute to hemodynamic and respiratory changes during carbon dioxide pneumoperitoneum. The aim of the present study was to evaluate the hemodynamic and respiratory effects of pneumoperitoneum (PP) with an intra-abdominal pressure (IAP) of 12 mmHg in children undergoing robot-assisted laparoscopic fundoplication during total intravenous anesthesia. Ten childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Previous studies have reported the safety and feasibility of robot-assisted antireflux surgery in children [1][2][3][4][5][6]. The first report on a randomised study [2] concluded that there was no obvious added benefit from the robotic technique compared with laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the safety and feasibility of robot-assisted antireflux surgery in children [1][2][3][4][5][6]. The first report on a randomised study [2] concluded that there was no obvious added benefit from the robotic technique compared with laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Transperitoneal insufflation pressures up to 10 mmHg do not induce significant hemodynamic changes [9,71,79], while insufflation pressures greater than 10 mmHg do not increase workspace in infants [64]. Pressures up to 12 mmHg have been reportedly well tolerated in patients aged 8-16 years [80].…”
Section: Pneumoperitoneum and Ventilation Strategiesmentioning
confidence: 95%
“…Firstgeneration robotic systems are immature for ideal pediatric use [25,26]. Early adopters and enthusiasts of robotic surgery no doubt see the future potential [26].…”
Section: Awaitmentioning
confidence: 99%